The Influence of Environmental Quality in Classrooms on Internal Response and Academic Performance in Conventional and Energy-Efficient Buildings - Ananda Karuna Jaya; Ramadhani Fithratullah; Kurniawati Kurniawati; Maria Ariesta Utha (International Journal Labs, 2023)
Humans spend a lot of time indoors, and this cannot be separated from teaching and learning activities. Teaching and learning activities must be conditioned so that the best academic performance can be achieved through adequate aspects of indoor environmental quality. The purpose of this study is to analyze the relationship between Indoor Environmental Quality (IEQ) on internal responses and academic performance in classrooms in two different building types. Where one building is a conventional building and the other building is a building that applies the concept of energy saving. A qualitative method was used in this research by conducting interviews with a purposive sampling technique then the results of the interviews were analyzed using a thematic analysis approach. The results of this study reveal that perceived comfort conditions are stated to positively affect the physiological, cognitive, and emotional status as well as the academic performance of students and lecturers, and high-efficiency buildings are more satisfying than conventional buildings.